PENGARUH RELIGIOSITY DIMENSION TERHADAP ATTITUDE TOWARDS FASHION PADA KONSUMEN MUSLIM DI SURABAYA - Badi Cahyo; Dudi Anandya; Silvia Margaretha (Perpustakaan Universitas Surabaya, 2020)
Indonesia is the majority of the country's population of Islam, even as many as 13% of Muslims in the world are citizens of Indonesia. Therefore, the purpose of this study was to examine the effect of religiosity dimension on attitude towards fashion on Muslim consumers in Surabaya. This research uses purposive sampling technique which is a sampling technique based on consideration or personal assessment of the researchers related to the characteristics of the appropriate population to be used as research samples. The characteristics are respondents who have been paying attention, follow and buy fashion products in Surabaya at least 1 year. Respondents in this study amounted to 278 people. Analysis in this study using SEM and processed using software version SPSS 18.0 and LISREL version 8.70 for measurement and structural testing. The results of this study indicate that 4 of the 5 hypotheses are not supported, namely ritualistic dimension and experiential dimension toward attitude towards fashion.